THE USED OF E-PROCUREMENT SYSTEMS IN GOVERNMENT AGENCIES: ISSUES AND CHALLENGES - Suzei Bt Mat Nuruddin; Zarina Bt Mohd Zain; Nur Alia Bt Mohd Nasir; Izzrin Nur Farhana Bt Rosman; Nor Suhaiza Bt Md. Khalid (International Journal of Accounting, Finance and Business, 2020)
Procurement can be defined in various ways and the procurement function is involving the activities and process of gaining the products, services and works. The main goal of procurement is to get the right categories of procurement at the right time, specific location and also carrying out the process effectively and efficiently. In recent decades, there is so many issues in government and this issue of procurement are increasing from time to time as it is become a trend of corrupt practices and abuse of power involving government agencies. Public Eprocurement is one of the important factors in public procurement reform and can play significant supporting role in making governments more transparent and accountable. E- procurement is seen as an effective way to better support transparency and accountability. In conjunction, even though Malaysia already implement e-procurement system but still there is high rate of procurement issue. So there must be lacking toward the system itself. Hence, the main purpose of this study is to study the ineffectiveness of e-procurement system in Malaysia. This research focus on the reasons for ineffectiveness of the systems and try to identify the impact from the poor system used in procurement. Finally, this research also aims to evaluate action taken by government in order to solve the ineffectiveness of e-procurement system. Ten informants been selected using purposive sampling technique. The informants been given a list of semi-structures questions before an interview session been conducted. The informants been selected from several government agencies in Negeri Sembilan such as Jabatan Keselamatan dan Kesihatan Pekerjaan Negeri Sembilan, UiTM Seremban Campus, UiTM Rembau Campus, Kementerian Kemajuan Luar Bandar dan Wilayah Negeri Sembilan and Jabatan Pelajaran Negeri Sembilan. From the findings it shows that reasons for ineffective system of procurement due to lack of standardization and complicated procedures. In addition, most of the staff still lack of skills in using the system. Some of the staff also are not accountable in control the systems especially during bidding process and the main contributor to ineffectiveness of e- procurement is because of barriers in ICT infrastructures. The impacts from e-procurement system that not effective, it will lead to corruption issues that still increase due to unfairness towards the qualified suppliers and small-scale contractors. To solve the problems, it was suggested for the staff to be sent for training and can enhance in term of management audit to view the performance of the staff in using the system. Despite, the management can have instant maintenan